2011
DOI: 10.2174/1874829501104010141
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Exposure to Mercury of the Adult Population in Mugusu Artisanal Gold Mining Village, Tanzania: A Total Diet Approach

Abstract: Gold extraction by artisan miners in different parts of Tanzania is widely done by mercury amalgamation technique. To the people living in and around the mining cites there is a potential for exposure to contamination through consumption of Hg contaminated food stuffs. Current studies on estimates of dietary human exposure to mercury in these areas have been limited to contributions of Hg contaminated fish consumption centrally to WHO recommendation on the use of Total Diet Studies. In this study dietary Hg in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 18 publications
1
13
0
Order By: Relevance
“…Machiwa [20] reported that many agricultural fields located near mining site in Geita and Tarime districts are contaminated with heavy metals. In Tanzania, major gold mines are located in Geita, Musoma, Kahama, Tarime, Chunya and Mpanda [21] which are also main food crops producing areas. Therefore, food crops cultivated near these gold mines are vulnerable to contamination with heavy metals.…”
Section: Sources Of Contaminationmentioning
confidence: 99%
See 4 more Smart Citations
“…Machiwa [20] reported that many agricultural fields located near mining site in Geita and Tarime districts are contaminated with heavy metals. In Tanzania, major gold mines are located in Geita, Musoma, Kahama, Tarime, Chunya and Mpanda [21] which are also main food crops producing areas. Therefore, food crops cultivated near these gold mines are vulnerable to contamination with heavy metals.…”
Section: Sources Of Contaminationmentioning
confidence: 99%
“…Mining activities contribute to the increase of levels of heavy metals in the agricultural soils [22] High level of Hg in agricultural soils in Mugusu gold mining in Geita District is influenced by mining activities [21] Deposition of industrial waste on the agricultural soils leads to the increase of heavy metals on the agricultural soils [1] Lake Victoria basin wetlands in Tanzania are highly contaminated with heavy metals through runoff from industrial waste disposal [1] Phosphate fertilizers produced in Tanzania consists of Hg, Cd, As, Pb, Cu and Ni, these may increase levels of these heavy metals to the soils [30] Application of phosphate fertilizers increased levels of As, Cd and Pb on paddy soils of North of Iran [31] …”
Section: Fact Findingmentioning
confidence: 99%
See 3 more Smart Citations